The case for Biblical Archaeology uncovering the historical record of God's Old Testament people - Currid, John D. 1951- (Phillipsburg, New Jersey P&R Publishing, 2020)
"We gain encouragement and helpful background to Scripture in studying the land of the Bible (the "fifth gospel"). Archaeologist and biblical scholar John Currid overviews areas of inquiry and discovery"--
Setting: Geography of the land of the Bible -- The archaeological study of the land of the Bible -- Tell excavation -- A short history of the lands of the Bible -- A journey through the land: Galilee / the Sea of Galilee region -- The Jezreel valley -- The Negev -- The Shephelah -- The Jordan River valley -- The southern coastal plain -- The central highlands -- Aspects of society: Agriculture and herding -- Water -- Architecture -- Ceramics -- The Hebrew language in archaeology -- Burial practices -- Small finds -- Appendices: Basic timeline of the ancient near east -- The kings of Israel and Judah -- Extrabiblical references to the kings of Israel and Judah.
Includes bibliographical references (pages 251-252) and indexes
Keywords: Bible -- Antiquities; Bible -- Geography; Bible -- Criticism, interpretation, etc; Bible -- History of Biblical events; Bible - Antiquités; Bible - Géographie; Bible - Histoire des événements bibliques; Bible; Bible; Excavations (archaeology) -- Palestine; Fouilles (Archéologie) - Palestine; Antiquities; Excavations (archaeology); Geography; History of Biblical events; Criticism, interpretation, etc; Palestine -- Antiquities; Middle East -- Antiquities; Excavations (archaeology) -- Middle East; Palestine - Antiquités; Moyen-Orient - Antiquités; Middle East; Middle East - Palestine